Analysis of the Village Head's Leadership in the Implementation of The Poverty Alleviation Program in North Malingping Village - Leni Indrawati; Euis Wulandari (CV. Lenggogeni Data Publishing, 2024)
This study aims to analyze the leadership of the Village Head in implementing poverty alleviation programs in Malingping Utara Village, Malingping District, Lebak Regency. The village head plays a strategic role in determining the direction of village development policies, including poverty alleviation as a central issue in local development. This research applies leadership theory using a qualitative descriptive approach. The key informants consist of the Village Head, village officials, neighborhood leaders (RT/RW), and program beneficiaries. Data were collected through in-depth interviews, observation, and documentation, then analyzed using data reduction, data presentation, and inductive conclusion techniques. The results show that the Village Head’s leadership style tends to be participatory and communicative, which positively affects the effectiveness of poverty alleviation programs. However, some challenges remain, such as data validation issues and limited community involvement during program evaluation. Overall, adaptive and open leadership has proven to support the achievement of program objectives more effectively.